Necrobiosis lipoidica: A clinicopathological study in the Indian scenario - Mary Thomas; Uday Sharadchandra Khopkar (Wolters Kluwer Medknow Publications, 2013)
Context: Necrobiosis lipoidica (NL) is a chronic granulomatous dermatitis that is commonly associated with diabetes mellitus. Most of the current knowledge about this entity is from western literature. Aims: This study evaluates the clinicohistological features of NL in an Indian scenario. Materials and Methods: We retrospectively reviewed clinical features, associated comorbidities, and biopsies of all patients with NL over a period of one year. Results: Five cases of NL were seen during the duration of the study. The preliminary clinical diagnosis ranged from sarcoidosis to tinea incognito. The commonest clinical presentation in the Indian scenario was of asymptomatic erythematous to skin-colored plaques and nodules on the shins with or without central atrophy. The most common site of involvement was the shin (3 of 5 patients). NL was associated with Diabetes mellitus in only two cases, both of whom were male patients. On histology, various patterns of inflammation were seen including the palisading, interstitial, and mixed granulomatous infiltrates. One patient had sarcoidal granulomas in association with an interstitial pattern. Features seen consistently in all cases include perivascular lymphoplasmacytic infiltrates, interstitial lymphocytic infiltrates, and fibroplasia. Interstitial mucin deposition was not observed in any of the biopsies. Conclusion: The diagnosis of NL was missed in most cases due to the rarity of the disease, absence of concomitant diabetes, and atypical presentations. Histology was a useful tool in clinching the diagnosis.